“WE ARE SO YOUNG”: : MANAGING DIFFERENT GENERATIONS IN ORGANIZATIONS - Cristina Gularte Liberato , Carla (Revista Gênero e Interdisciplinaridade, 2021)
21st century marked by technological advances, anxiety, stress, conflicts, different generations living in the same organizational environment. Daily challenges to extraordinary leaders, capable of using differences and conflicts in favor of companies. Using refined tools and techniques combined with good active listening, you are able to evolve daily in the frantic world. Caoching, mentoring, skills and knowledge management, feedback and feedforward are allies in this process.